2012
DOI: 10.18433/j37k5w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Potential Drug-Drug Interactions in the Elderly: A Cross-Sectional Study in the Brazilian Primary Public Health System

Abstract: Purpose. The primary objective of this study was to investigate the prevalence of clinically important potential drug-drug interactions (DDIs) in elderly patients attending the public primary health care system in Brazil. The secondary objective was to investigate possible predictors of potential DDIs. Methods. A cross-sectional study was carried out in 5 Brazilian cities located in the Ourinhos Micro-region, Sao Paulo State, between November 2010 and April 2011. The selected sample was divided according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
7
28
1
2
Order By: Relevance
“…Similar to previous Brazilian studies, our sample presented a high prevalence of chronic diseases, with hypertension, diabetes and dyslipidemia being the most common ones (Rozenfeld, Fonseca, Acurcio, 2008, Obreli-Neto et al, 2011, Obreli-Neto et al, 2012b. The high prevalence of chronic diseases is onerous for the health system, a fact also encountered in other studies with elderly patients (Leite-Cavalcanti et al, 2009;Crentsil et al, 2010), and should serve as an alert for health service planning due to the process of population ageing, since chronic diseases require continuous treatment and monitoring (Abegunde, Stanciole, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to previous Brazilian studies, our sample presented a high prevalence of chronic diseases, with hypertension, diabetes and dyslipidemia being the most common ones (Rozenfeld, Fonseca, Acurcio, 2008, Obreli-Neto et al, 2011, Obreli-Neto et al, 2012b. The high prevalence of chronic diseases is onerous for the health system, a fact also encountered in other studies with elderly patients (Leite-Cavalcanti et al, 2009;Crentsil et al, 2010), and should serve as an alert for health service planning due to the process of population ageing, since chronic diseases require continuous treatment and monitoring (Abegunde, Stanciole, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…Of the 47 records resulting from the search strategies, 24 (51.1%) full-text articles were retrieved for review concerning ADR 11 - 18 , 20 , 24 - 25 , 28 - 29 , 34 - 36 , 38 - 40 , 46 , 51 - 52 , 54 , 56 ) , 14 (29.8%) DDI 21 - 23 , 27 , 30 - 33 , 41 , 43 - 45 , 49 , 53 and nine (19.1%) are related to both DDI and ADR 19 , 26 , 37 , 42 , 47 - 48 , 50 , 55 , 57 , according to Figures 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…A number of other studies have also identified an increase number of medications a predictor of DDI in the elderly [6, 9, 15, 30, 3441]. A study from Brazil reported that the potential drug interaction risk when patients are taking 2–3, 4–5 and 6–7 medications was 39, 88.8 and 100 %, respectively [36].…”
Section: Discussionmentioning
confidence: 99%
“…Though the incidence of actual DDIs is lower than that of potential DDIs, some studies have found as high as 25–47 % clinically relevance potential DDIs in the elderly [33, 41]. The occurrence of clinically important interactions depends in the presence of specific risk factors such as polypharmacy, comorbidity, age, therapeutic range and dosage of the drug [42].…”
Section: Discussionmentioning
confidence: 99%